Assessing economic research and the future of heterodox economics. Failures and alternatives of journals, departments, and scholars rankings - Wolfram Elsner; Fred Lee (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: Evaluating economic research today is a most contested field. This applies, most notably, since individual careers of a whole generation of critical young economists are affected. And it applies in economics, perhaps more than in any other discipline, since it is the most important academic discipline for the ideological legitimization of capitalism and one of the few, perhaps the only, fundamentally divided and contested discipline. What the ruling forces of the economy, of professional politics, of science administration, and particularly of economic science have made out of the complex issues and processes of evaluating research quality is reducing them down to a simplistic, allegedly exact, objective, and obvious, but fundamentally mistaken procedure of a one-dimensional ranking of quantitative domination, a cumulative dictatorship of mass. And this is done in surprisingly unprofessional ways, subject to many obvious misconceptions and failures. For example, the International Mathematical Union, the International Council of Industrial and Applied Mathematics, and the Institute of Mathematical Statistics have argued in a joint report released in June 2008 that »the belief that citation statistics are accurate measures of scholarly performance is unfounded«, the »use of such statistics is often highly subjective«, »the validity of these statistics […] is neither well understood nor well studied«, and »that sole reliance on citation data provides at best an incomplete and often shallow understanding of research«. In the same vein, economist Bruno Frey found »that such rankings do not effectively measure research quality«, and »career decisions based on rankings are dominated by chance« (Frey/Rost 2008).
Keywords: 330